Room-Temperature Nonreciprocal Charge Transport in an InAs-Based Rashba Channel - Ahn, Jeong Ung; Han, Ki Hyuk; Kim, Seong Been; Lee, OukJae; Kim, Hyung-jun; Koo, Hyun Cheol (Electrochemical Society, Inc., 2022)
Nonreciprocal charge transport is observed in a non-centrosymmetric system without a ferromagnetic layer. To observe the nonreciprocity of the Rashba system, an InAs-based two-dimensional electron gas channel is utilized and the angular dependent harmonic Hall measurement is performed. From the amplitude of the curve, a nonreciprocal coefficient of 1.36 A(-1)T(-1) is extracted at 1.9 K. While the extracted value of the nonreciprocal coefficient decreases down to 0.44 A(-1)T(-1) at 300 K, we can clearly observe the nonreciprocal charge transport at room temperature. In addition, the independent transport measurements clarify that the amplitude of nonreciprocal coefficient is closely connected with the strength of the Rashba effect.